Is it a man´s world? Exploring Portuguese female gamer's perception's and experience regarding sexism in the gaming - Valente, Verónica (2022)
Objective: The analysis aimed to understand Portuguese gamers’ perceptions of sexism in the world of gaming, focusing on the female perspective regarding existing gamer gender stereotypes and their experiences with online harassment while playing digital role-playing games (RPGs). Design and Method: This qualitative study comprised of 14 semi-structured interviews with individuals who identify as females between the age of 18 to 42 (M = 26.1; SD = 5.9) from different regions in Portugal which currently self-identified as gamers. Results: Two main themes emerged from the thematic analysis of the interview transcripts: (a) gamer gender stereotypes and (b) types of sexism between gamers. When reflecting on female gamer stereotypes, these were described negatively within the community and their competence to play is often questioned based on gender difference. Beyond this, results showed how gamers perceive types of sexism differently according to context, often partaking in benevolent sexism to alleviate the negative connotation of sexism provided by humor and sexist compliments. However, female gamers rendered multiple personal descriptions of hostile sexism and sexual objectification combined leading to online sexual harassment by their fellow male gamers while playing. These findings shed light on the issues of access to online resources and social equality for women in the gaming community and its male-driven culture, pointing to its flaws and a need for intervention to establish a safer place for all gamers. Conclusions: The findings offered an insight on the issues faced by female gamer in a video game setting, by withstanding judgment when stereotypes, and by having to face hostile attitudes from fellow gamers, not singularly male gamers. The behavior focused on gender differences and often alluded to sexual objectification to make the female gamers uncomfortable, flowed by attempts to establish an unrequired intimacy.